Effects of particle aspect ratio on pyrolysis and gasification of anisotropic wood cylinder. (15th June 2015) - Pattanotai, Teeranai; Watanabe, Hirotatsu; Okazaki, Ken
Highlights: Effects of wood aspect ratio (length/diameter) on pyrolysis and gasification are discussed. X-ray computed tomography is used to visualize the 3D anisotropic structure of chars with various aspect ratios. The total tar yield from pyrolysis decreases with an increasing aspect ratio. Char reactivity during gasification increases with a decreasing aspect ratio. Role of anisotropic structure of woody biomass is relevant to aspect ratio. Abstract: In this study, the effects of particle aspect ratio (length/diameter) of a wood cylinder on pyrolysis and gasification characteristics were experimentally investigated. X-ray computed tomography was used to visualize the structure of char with different aspect ratios. Small and uniform pores were observed near the surface, whereas the size and shape of majority of the middle pores were large and random. Regardless of the aspect ratio, the pores generally aligned along the axial direction of wood cylinders. In the pyrolysis process, the total tar yield was found to decrease with an increasing aspect ratio. This was due to the tar being transported predominantly through the axial pores; therefore, wood cylinders with a high aspect ratio provided a long residence time for intraparticle tar decomposition, resulting in a lower tar yield. An Arrhenius plot of char reactivity during gasification revealed an aspect ratio effect in the internal-diffusion controlled zone (zone II), which did not appear in the kinetically controlled zone (zone I). Char reactivity increased with a decreasing aspect ratio in zone II. The gasifying agent primarily penetrated into the char through the top and bottom surface of the wood cylinder as a result of the pores aligned along the axial direction. The role of anisotropic structure of woody biomass was relevant to its aspect ratio.